1979
DOI: 10.1007/bf00563114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a combination of doses of fenoterol and ipratropium suitable for a single metered-dose aerosol

Abstract: This paper reports a study of the bronchodilator effects of doses of the beta 2 agonist fenoterol and the muscarinic blocker ipratropium suitable for administering in combination as a standard dose of two discharges from a single metered-dose pressurised aerosol. In 12 middle-aged bronchitics who had already been shown to respond to both types of drug the combination was almost always a little (6% on average) more effective than either drug singly. It is possible that an equal or better effect could have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated that the combination of IB and fenoterol has a more potent and long-lasting bronchodilator effect than that of each individual drug [1,3]. The patients with asthma can be differentiated, on the basis of response to inhaled bronchodilator, into 'flow re sponders', i.e., those with a prevalent in crease in How, and 'volume responders', i.e., those with a prevalent increase in forced expiratory volumes; IB could have a major bronchodilator effect on central airways with a prevalent increase in forced expiratory volumes, while fenoterol could have a prevalent action on small airways with increase in flows [5,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the combination of IB and fenoterol has a more potent and long-lasting bronchodilator effect than that of each individual drug [1,3]. The patients with asthma can be differentiated, on the basis of response to inhaled bronchodilator, into 'flow re sponders', i.e., those with a prevalent in crease in How, and 'volume responders', i.e., those with a prevalent increase in forced expiratory volumes; IB could have a major bronchodilator effect on central airways with a prevalent increase in forced expiratory volumes, while fenoterol could have a prevalent action on small airways with increase in flows [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, in the last few years several studies have demonstrated that a combination between an anticholinergic and a beta-adrenergic drug, like Duovent, is useful in obtaining more effective ther apeutic action and/or reducing the single drug doses [1,3]. Only few data are avail able on this combination and the develop ment of tolerance, i.e., a decreased respon siveness to the drug occurring with predic table frequency when specific receptors are chronically stimulated by prolonged therapy with inhaled Duovent.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the combined use of ipratropium bromide and bela^-agonists, showing a greater or more prolonged response than that which occurred with individual drugs [Addis et al, 1979;Pierce et al, 1979]. According to previous reports, we have observed in our patients a greater persistence of broncho dilating action with Duovent than with terbutaline, as shown by the comparison of the basal values on the 7th and 14th days for the majority of parameters ex amined, without reduction in pharmaco dynamic response following inhalation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of fenoterol and ipratropium bromide has been shown to produce a greater bronchodilator response than that achieved by either agent alone both in asthma (Martin, Berend and Harrison, 1979) and chronic bronchitis (Addis, Barclay and Chang, 1979;Anderson, Jariwalla and Turnbull, 1980). This combination has recently become available in a single metered dose inhaler.…”
Section: Introductionmentioning
confidence: 99%